JARE RELA (STRUCTURED WALK, FOOT SOAK OF WARM WATER AND DEEP BREATH RELAXATION) - Abdillah, Alvin; Priyanto, Agus (STIKES NGUDIA HUSADA MADURA, 2024)
Hypertension is a major risk factor for the development (cause) of heart disease and stroke that often occurs in the elderly, cases of hypertension are increasing in Indonesia. The purpose of this community service is to apply the results of previous research, namely overcoming the problem of hypertension with structured walking methods, warm water foot soak and deep breath relaxation. The results of the intervention carried out in community service after evaluation found that most of the elderly are able and willing to carry out structured walking, warm water foot baths and deep breath relaxation. Thus, it can be concluded that this community service activity was successfully carried out well.